Neighbourhood cohesion as a form of privilege. (June 2021) - Méndez, María Luisa; Otero, Gabriel; Link, Felipe; López Morales, Ernesto; Gayo, Modesto
Contrary to the idea that neighbourhood cohesion is something that inherently benefits the poor or counterbalances the forces of social exclusion, in this article we argue that it can also function as a mechanism of cumulative advantage. In order to explore this proposal, we offer a definition and key dimensions of neighbourhood cohesion based on three components: place attachment, local relations and commitment to the local common good. We test our proposal in a highly segregated Latin American city: Santiago, Chile. A combination of survey data and georeferenced information was obtained from a random sample of 700 residents. The results reveal the existence of four neighbourhood cohesion types: Communitarians, Belongers, Strangers and Outsiders. As expected, we found that people who reside in affluent areas and perceive themselves to live in more reputable neighbourhoods are those who report the strongest patterns of neighbourhood cohesion. We conclude by questioning the scope and effectiveness of policies which have promoted neighbourhood cohesion as a 'tool' of governance without first attempting to reduce socio-spatial rifts. We also ask whether these notable spatial differences in neighbourhood cohesion contribute to improving the overall social cohesion at the city level.